DEVELOPMENT AND VALIDATION OF AN ANALYTICAL METHOD FOR THE DETERMINATION OF METHYLISOTHIAZOLINONE AND METHYLCHLOROISOTHIAZOLINONE IN COSMETIC PRODUCTS USING MATRIX SOLID-PHASE DISPERSION COUPLED TO GAS CHROMATOGRAPHY-MASS SPECTROMETRY - PRAPURANDINA, NURINA; HARMITA, HARMITA; SURYADI, HERMAN (International Journal of Applied Pharmaceutics, 2021)
Objective: This study was to develop the first simultaneous method for quantification of MI and MCI by using matrix solid-phase dispersion (MSPD) as an extraction technique followed by gas chromatography-tandem mass spectrometry (GC-MS) in cosmetic products to support that law enforcement. Methods: The MI and MCI were extracted from the cosmetic sample by using matrix solid-phase dispersion technique with alumina as solid sorbent and ethyl acetate as eluent. After being isolated, MI and MCI from the samples were analyzed using GC-MS equipped with DB-5MS capillary column. Results: The validated method for both leave-on and rinse-off cosmetic showed that MI and MCI recoveries were between 97.87-103.15 %, relative standard deviation (RSD) values were lower than 11%, and limit of quantitation (LOQ) values for the leave-on product were 0.96 µg/ml and 1.95 µg/ml and for rinse-off products were 0.56 µg/ml and 1.49 µg/ml for MI and MCI, respectively. Conclusion: This purposed analytical method for determining MI and MCI in cosmetic products using MSPD-GC-MS complies with the validation acceptance criteria.